Состояние ценопопуляций Festuca valesiaca Gaudin в зависимости от режима использования - Ибатулина, Ю.В. (Промышленная ботаника, 2004)
The article represents a characteristic of steppe sites where material collections were conducted. Density, age structure and type of Festuca valesiaca Gaudin cenopopulations, dominant species, one of the edificators of steppe phytocenoses have been determined. The variability of age structure of dense-cespitose graminoid cenopopulations, depending upon anthropogenic load, has been investigated. The age structure of the given species cenopopulations is stable within wide diapason of elogie-andcoenotic conditions, its deep changes being possible under considerable anthropogenic and natural impact.